EP 38. Voxel-based morphometry reveals increased gray matter density in the uvula in physiological upbeat nystagmus. Issue 9 (September 2016) - Rühl, R.M.; Stephan, T.; Dieterich, M.; Zu Eulenburg, P.
Abstract : Aim: Some videooculography (VOG) studies have reported a spontaneous upbeat nystagmus (UBN) in the absence of fixation in a number of healthy subjects (Bisdorff et al., 2000 ). These oscillations of the vertical gaze system are thought to be under the influence of the gravitational force vector, termed vestibular nystagmus. The neural basis of this UBN and whether structural differences can be attributed to it, however, remain unclear. Aim of our combined voxel-based morphometry (VBM) and VOG approach within the context of a larger vestibular stimulation study was to investigate the anatomical substrate of this UBN in healthy subjects. Methods: 44 right-handed healthy subjects (21 F; mean age 28 years) were examined in supine position by means of VOG (EyeSeeCam©) without fixation before and after bimastoidal galvanic vestibular stimulation (GVS). Then structural and functional images were obtained in a clinical 3T scanner (Siemens Magnetom Verio, Erlangen, Germany) with a 32-channel head coil. The protocol included an isotropic (1 × 1 × 1 m) MPRAGE sequence and a resting-state session with 165 volumes, each consisting of 36 slices of a T2 ∗ -weighted ascending EPI sequence (TR 2.31s). Data analysis was performed using the VBM12 toolbox within SPM 12 (Version 6407 Wellcome Department of Imaging Neuroscience, London, UK) in Matlab 2015b (The MathWorks, Natick, Massachusetts, USA) after standard preprocessing. T-contrasts were calculated with respect to the rest condition and were considered significant at p < 0.05 (corrected at cluster level). Results: In the VOG experiment, a spontaneous UBN occurred in 20 of 44 subjects (9 F) with a mean slow phase velocity (SPV) of 2, 3°/s (SD = 1.1). After GVS, SPV decreased significantly by 52% (mean reduction of SPV = 1.06 °/s, SD = 1.0; paired t(19) = 0.03, p < 0.05). VBM analysis revealed a significant cluster (p= 0.05 FDR) of increased grey-matter density information in the left uvula in subjects with UBN, whereas subjects without UBN showed a significant increase in grey matter volume in the right cerebellar tonsil and left inferior semilunar lobe. In a separate analysis for subjects with UBN, a significant positive correlation was found between the grey matter volume of the left uvula and the degree of UBN reduction after GVS. The left cerebellar tonsil on the other hand showed a negative correlation. Conclusion: Individual structural differences in the uvula could account for the physiological UBN in the absence of fixation in supine position. The uvula contributes to the processing of otolith information and responds both to translation and changes in orientation relative to gravity (Angelaki et al., 2004 ). The tonsil on the other hand seems to be crucial for gaze-holding. Our results point to the importance of a balanced interplay of uvula and tonsil in vertical gaze control. The combination of a minimized influence of gravity on vertical eye movements in supine position and the absence of visual information might demask central oscillatory signals within the vertical gaze system. High frequency dampening via GVS might in return result in an artificial external stabilization of this system, reflected in a decrease of UBN. Supported by the German Foundation for Neurology (DSN) and the German Research Foundation.